Thyroid dysfunction in young, first-episode and drug-naïve patients with major depressive disorder: prevalence and associated clinical factors - Wu, Jinbo; Wang, Zhunian; Xu, Hongjiao; Yang, Liying; Liu, Jiacheng; Zheng, Yue; Kang, Chuanyi; Wang, Xiaohong; Shi, Jingjing; Zhao, Na; Zhang, Xiang Yang (Frontiers in Psychiatry, 2023)
Objective The incidence of thyroid dysfunction (TD) and major depressive disorder (MDD) is increasing year by year in the general population. However, the prevalence and correlates of TD in first-episode drug-naive (FEDN) MDD patients have not been explored. This study sought to fill this gap and examine the association between TD and MDD. Methods We recruited 1,289 FEDN MDD patients aged 18 ~ 45 years. A total of 1,289 FEDN MDD outpatients were recruited. Demographical and suicide data were collected for each patient, and lipid profiles, thyroid function, and fasting blood glucose (FBG) levels were measured. The Hamilton Depression Scale 17 (HAMD-17) was assessed for depression. Results The prevalence of TD in young FEDN MDD patients was 64.86%. Compared with those without TD, patients with TD had longer duration of illness, greater HAMD score, higher BMI, TG, TC, and LDL-C levels, and higher suicide attempt rates, but lower HDL-C and FBG levels. Further logistic regression indicated that duration of illness, HAMD score, TC, HDL-C, BMI, and FBG levels were significantly associated with TD. Limitations No causal relationship can be drawn due to the cross-sectional design. Conclusion TD is common in young FEDN MDD patients. So clinicians should monitor thyroid function in patients with MDD.